2021
DOI: 10.3389/fnagi.2021.600484
|View full text |Cite
|
Sign up to set email alerts
|

Elamipretide (SS-31) Improves Functional Connectivity in Hippocampus and Other Related Regions Following Prolonged Neuroinflammation Induced by Lipopolysaccharide in Aged Rats

Abstract: Neuroinflammation has been recognized as a major cause for neurocognitive diseases. Although the hippocampus has been considered an important region for cognitive dysfunction, the influence of hippocampal neuroinflammation on brain functional connectivity (FC) has been rarely studied. In this study, lipopolysaccharide (LPS) was used to induce systemic inflammation and neuroinflammation in the aged rat brain, while elamipretide (SS-31) was used for treatment. Systemic and hippocampal inflammation were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…In our study, a significant correlation was observed between FC and CRP, and management based on multimodal brain monitoring may have prevented an increase in the post-operative LPS level. The results of the current study and our previous work indicate that management based on multimodal brain monitoring during surgery may improve brain FC by reducing neuroinflammation in aged patients (Fu et al, 2014;Kan et al, 2016;Liu et al, 2021).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In our study, a significant correlation was observed between FC and CRP, and management based on multimodal brain monitoring may have prevented an increase in the post-operative LPS level. The results of the current study and our previous work indicate that management based on multimodal brain monitoring during surgery may improve brain FC by reducing neuroinflammation in aged patients (Fu et al, 2014;Kan et al, 2016;Liu et al, 2021).…”
Section: Discussionsupporting
confidence: 63%
“…Meanwhile, the application of NF-κB pathway blocker pyrrolidine dithiocarbamic acid reduced the levels of inflammatory cytokines in the Hip and the expression of postsynaptic density (PSD)-95, and improved long-term cognitive function in aged rats exposed to LPS (Kan et al, 2016). FC in aged rats is related to cognitive function, which may be exacerbated by neuroinflammation induced by a systemic inflammatory response (Liu et al, 2021). In our study, a significant correlation was observed between FC and CRP, and management based on multimodal brain monitoring may have prevented an increase in the post-operative LPS level.…”
Section: Discussionmentioning
confidence: 99%
“…As such, further investigation of the role of different glial cells in these functional changes could improve our understanding of multicellular dynamics associated with neuroinflammatory mechanisms. Further, the disruption of community structure of microcircuits may have broad implications for the role of glia in cognitive impairments exhibited after LPS exposure in both rats and humans 49,50,53,64 .…”
Section: Discussionmentioning
confidence: 99%
“…While LPS-induced neuroinflammation does not model a specific disease pathology, it can add to our understanding of basic neuroinflammatory cellular dynamics. LPSinduced neuroinflammation has significant downstream effects on neural function, including connectivity changes in mesocircuits [49][50][51] , the development of epileptiform hyperactivity 52 , and cognitive deficits in rodents and humans 49,53 . Here, we examined the effect of LPS on microcircuit FC in microtissues.…”
Section: Functional Connectivity Significantly Increases 5-9 Days After Lps Exposurementioning
confidence: 99%
“…SS-31 reduced Aβ production and mitochondrial dysfunction, restored mitochondrial dynamics, and enhanced mitochondrial biogenesis and synaptic activity in AD mice [ 186 , 187 ]. SS-31 was recently shown to ameliorate mitochondrial dysfunction and synaptic and memory impairment induced by neuroinflammation [ 188 , 189 ]. Despite its success in preclinical trials in aging and related health conditions, clinical trials of SS-31 have not been successful so far (tested in heart failure and primary mitochondrial myopathy).…”
Section: Mitochondria-targeted Therapies In Admentioning
confidence: 99%